2017
DOI: 10.1177/1359105317745963
|View full text |Cite
|
Sign up to set email alerts
|

Female condom acceptability in urban India: Examining the role of sexual pleasure

Abstract: This qualitative study examined the acceptability of female condoms in urban India, with a focus on sexual pleasure. We conducted focus group discussions with 50 women and 19 men, as well as a small number of individual interviews with women (n = 3), in Chennai and New Delhi. Perceived benefits of female condoms included protection against unintended pregnancy and sexually transmitted infections, increased sense of empowerment for women, and simple clean up. The most common drawback was reduced sensation. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…While most studies exploring the experiences of women using the female condom have been conducted with specific communities or in low-income countries [ 8 , 17 , 25 ], this is the first study to examine the experiences of women in Australia. Findings may inform health promotion efforts, clinical consultations and sexual health counselling guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While most studies exploring the experiences of women using the female condom have been conducted with specific communities or in low-income countries [ 8 , 17 , 25 ], this is the first study to examine the experiences of women in Australia. Findings may inform health promotion efforts, clinical consultations and sexual health counselling guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is less accessible than the male condom as it is not widely available for purchase and is more expensive [ 6 , 7 ], it does offer several advantages. For instance, it can be used by those allergic or sensitive to latex [ 8 ], can be inserted into the vagina before sex and used with any type of lubricant [ 6 ], may enhance pleasure from clitoral stimulation [ 9 , 10 ], and it does not require an erect penis or immediate withdrawal after ejaculation [ 6 , 11 ]. While it has a higher failure rate than other modern methods of contraception, it is comparable to the male condom in terms of both contraceptive effectiveness [ 12 , 13 ] and STI prevention [ 6 ] and remains the only female-initiated method of dual protection [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that limit the acceptability of condoms include slippage, poor esthetics, lack of lubrication, pain on use and difficulty in insertion (Reece, Herbenick, & Dodge, 2009;Wanyenze et al, 2011;Peixoto, Botelho, Tomada, & Tomada, 2016;Bowling et al, 2018). In addition, there is a growing consensus that issues related to pleasure and condoms deserve to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…It has the potential to both empower women and please men [10]. Recent researches have shown that the female condom with trusted efficacy could increase the uptake of condom use, reduce stress caused by unintended pregnancy or STIs, and increase sexual pleasure and health benefits [11, 12]. Although female condoms have been marketed internationally since the mid-1990s, they remain relatively unpopular in China, for example, most migrants have never seen a female condom [13].…”
Section: Introductionmentioning
confidence: 99%